Arabic Songs as a Source of Vocabulary Exposure: A Textual Look at Their Lexical Patterns and Their Relevance for Learners at the Secondary Level - Salma Indah Maharani; Husnul Khotimah; Khoirunnisa Wahidah Syahputri; Siti Uriana; Kisno Umbar (Learning, Media and Technology in Arabic Education, 2025)
Background: Arabic pop songs are easy to find and often listened to by students, and this makes them an interesting source of natural vocabulary exposure. Their wording tends to be simple and repetitive, which raises the question of whether they can support early stages of Arabic learning. Aims: The study aims to look more closely at the kind of vocabulary that appears in several well known Arabic songs and to consider whether the language they contain is appropriate for learners at the secondary level. Methods: A qualitative textual approach was used to examine two songs by Humood Al-Khudher. The lyrics were read and classified carefully, with attention to basic lexical categories such as verbs and nouns. The findings were then compared with vocabulary taught in MTs and introductory pesantren Arabic courses. Result: The two songs turned out to contain a range of familiar word forms, including common imperatives, simple verb patterns, and nouns that appear frequently in standard textbooks. The lines in both songs repeat key expressions, which makes the language easier for students to absorb. Their motivational themes also help maintain student interest. Conclusion: The study suggests that Arabic pop songs can serve as a useful additional source of vocabulary for secondary-level learners. Their clarity and tone make them suitable for classroom support materials, although further research inside the classroom is still needed to see how students respond when the songs are actually used in teaching.